Dampak Kebijakan Pajak terhadap Preferensi Pertukaran Mata Uang Kripto: Analisis Kualitas dalam Konteks Regulasi yang Berkembang - Eri Kusnanto; Yessica Amelia; Seger Santoso (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This qualitative literature review examines the impact of tax policies on cryptocurrency exchange preferences within the context of evolving regulations. With the rapid growth of the cryptocurrency market, understanding the relationship between tax regulations and user behavior has become crucial. This study synthesizes findings from various research articles, highlighting how clear and transparent tax policies can influence user engagement and compliance in cryptocurrency trading. The review reveals that uncertainty regarding tax obligations often leads to user avoidance of cryptocurrency exchanges, while a better understanding of tax responsibilities correlates with more proactive investment management. Furthermore, the analysis indicates that cryptocurrency platforms demonstrating transparency in tax handling are preferred by users. The findings emphasize the necessity for governments to develop supportive tax frameworks and educational initiatives to facilitate healthy growth in the cryptocurrency sector. Overall, the research underscores the importance of regulatory clarity in fostering user trust and participation in cryptocurrency exchanges, ultimately contributing to a more robust and sustainable market.